Evaluation of Urea Super Granule as a Source of Nitrogen in Transplant Aman Rice (Progressive Agriculture, 2014)
An experiment was carried out at Bangladesh Agricultural University, Mymensingh to evaluate the effect of urea super granule (USG) as a source of nitrogen on the yield and yield components of transplant Aman rice cv. BRRI dhan39, BRRI dhan46 and BINA dhan7. Five levels of N (viz., 0, 60, 120 kg ha-1 as prilled urea and 60 and 120 kg ha-1 as USG) were taken as experimental treatments. The experiment was laid out in a randomized complete block design with three replications. Plant height, effective tillers hill-1, grains panicle-1 and grain yield varied significantly due to different cultivars. All the yield and yield components except 1000-grain weight were influenced significantly by the levels of nitrogen fertilizer. The highest grain yield (4.82 t ha-1) was recorded in BINA dhan7 and the lowest one (4.30 t ha-1) was recorded in BRRI dhan39. Nitrogen @ 120 kg ha-1 as USG performed the best among the treatments in respect of yield and yield components of rice. The highest grain yield (5.46t ha-1) was obtained from BINA dhan7 with 120 kg N ha-1 as USG which was statistically identical with 60 kg N ha-1 as USG. A considerable amount (31.25%) of prilled urea (PU) nitrogen could be saved by using USG. It may be concluded that USG could be used as N management to achieve better nitrogen use efficiency in reducing N loss than the PU.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19095 Progress. Agric. 24(1&2): 29 - 37, 2013